(3GdCMGOjK GdYTQhf GdYhGdis - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdLRi GdTGaYi gPG GMGOjK YTQhf GYdi eG hbY di ef GdGSfGO Edi GdfHi Udi Gddg Ydjg hSde hGYdG eG jhLO Gdjhe ai GdOfjG s
(3BNQgG (B:s
(3hGOYi Gfg ef GUMGH Ydi QVi Gddg Yfg cd Pdc eeG jcJH ddaQMI hGdVMc Yef GJaYdg Ch GYJbOg JeJ GdGMGOjK GdYTQhf s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeGe jMi HGdjef (B((3JGQjN (B6) s
Keywords: (3eJaQbGJs